2022
DOI: 10.1111/jam.15158
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilli reduce recurrences of vaginal candidiasis in pregnant women: a randomized, double-blind, placebo-controlled study

Abstract: Aims The aim of this study was to investigate the effects of lactobacilli strains in preventing the recurrences of vaginal candidiasis (VC) in 78 pregnant women with VC (lactobacilli, n = 39; placebo, n = 39) and the potential benefits on quality of life. Methods and Results The lactobacilli putative probiotic (SynForU‐HerCare; two capsules/day of 9·5 log CFU per capsule) or placebo was administered for 8‐weeks in a randomized, double‐blind, placebo‐controlled study. Subjects were assessed for vaginal and gut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…There are very few studies that have used probiotics alone to treat or prevent the recurrence of VVC [ 38 , 39 ], while most works have used probiotics as an adjunctive therapy after treatment with an antifungal drug [ 26 , 31 , 40 ]. However, the antifungal effect of probiotics has been reported in many studies [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are very few studies that have used probiotics alone to treat or prevent the recurrence of VVC [ 38 , 39 ], while most works have used probiotics as an adjunctive therapy after treatment with an antifungal drug [ 26 , 31 , 40 ]. However, the antifungal effect of probiotics has been reported in many studies [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study design population has been described previously [8]. Briefly, this was a randomized, double-blinded, placebo-controlled study, enrolling pregnant women at 14-32 weeks of pregnancy and confirmed with VC by an obstetrics and gynaecology specialist and/or a medical doctor.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…However, this has caused various concerns attributed to the emergence of drug-resistant yeasts, while prolonged exposure to fluconazole, as in cases of recurrences, can shift the predominant vaginal yeast flora from Candida albicans to more intrinsically azole-resistant species such as Candida krusei or Candida glabrata, typically in immunosuppressed women, and may be exacerbated in healthy women by use of over-the-counter products for self-treatment of VVC. Cross-resistance between OTC drugs (miconazole, clotrimazole, and tioconazole) and fluconazole has been observed in clinical isolates of C. glabrata and C. albicans [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increases the need for reliable in vitro methods to study the release of probiotics from such drug delivery systems and ensure that the probiotics stay alive during the in vitro study. The most common drug delivery systems for probiotics are the traditionally used capsules besides polymeric particles and microdevices [4,6,7].…”
Section: Hardware In Contextmentioning
confidence: 99%